Pembuatan Peta Suhu Permukaan Tanah untuk Mitigasi Urban Heat Island dengan Visualisasi Augmented Reality (Studi Kasus: Kota Surabaya) - Hanif, Muhammad; Hayati, Noorlaila; Bioresita, Filsa; Hidayat, Husnul; Hanansyah, Megivareza Putri; Jaelani, Lalu Muhamad; Sukojo, Bangun Muljo; Rahmansyah, Ferdian Zaki (Sarau Institute, 2025)
The Urban Heat Island (UHI) phenomenon in Surabaya is becoming increasingly apparent due to the conversion of green areas into built-up areas. This community service activity aims to map land surface temperature (LST) for the period 2016–2024 using Landsat 8 level 2 imagery and present it in augmented reality (AR) visualization to support public literacy. The analysis was conducted through calculations of NDVI, emissivity, LST, NDVI–LST linear regression, and field validation usinga thermohydrometer. The results show that the distribution of LST increased in 2016–2019, decreased in 2020, then increased again in 2021–2023 before decreasing in 2024. The negative correlation between NDVI and LST indicates that vegetation plays an important role in reducing temperatures. Field validation produced a coefficient of determination (R²) of 0.7213 with a maximum difference of 5°C between satellite data and measurements. The 2024 UHI map shows high intensity in densely built-up areas (Tegalsari, Genteng, Sawahan, Tambaksari, Wonokromo, and parts of Rungkut), while outlying areas like Benowo and Pakal are relatively cooler. AR-based visualizations have proven effective in helping the public and policymakers understand the UHI phenomenon more interactively and encouraging the development of mitigation strategies through reforestation and sustainable urban planning.